Profit and principle : Hugo Grotius, natural rights theories and the rise of Dutch power in the East Indies, 1595-1615 - Van Ittersum, Martine Julia, 1968- (Brill's studies in intellectual history, 2006)
This monograph is a study of the interaction of politics and political theory in The Netherlands and Asia in the early seventeenth century. Its focal point is the Dutch jurist Hugo Grotius (1583-1645), who developed his rights and contract theories for the benefit of the United Dutch East India Company or VOC. The monograph reconstructs the immediate historical context of his political thought, as conceptualized in his early manuscript De Jure Praedae/On the Law of Prize and Booty and Mare Liberum/The Free Sea (1609). It argues that Grotius' justification of Dutch interloping in the colonial empires of Spain and Portugal made possible the VOC's rise to power in the Malay Archipelago, which resulted in the slow, but steady, loss of selfdetermination on the part of the inhabitants of the Spice Islands.